Algorithm for the United Quality Latent Index of the plant adaptability and its application field in monitoring of Deschampsia antarctica È. Desv. populations - Miryuta, N.; Smykla, J.; Parnikoza, I. (Український антарктичний журнал, 2019)
Main objective of the research was to develop an algorithm for the United Quality Latent Index of Adaptability (UQLI, Iq) and to demonstrate its application on the study of Deschampsia antarctica È. Desv. at the monitoring site of Galindez Island, Argentine Islands, maritime Antarctic in natural setups. Мета дослідження — розробити і детально описати алгоритм розрахунку показника комплексної адаптованості — зведеного латентного показника пристосовуваності (ЗЛПП) та його застосування в оцінці пристосовуваності Deschampsia antarctica È. Desv. у природних умовах о. Галіндез, Аргентинські острови, Морська Антарктика.